Study of The Electrical, Optical and Morphological Properties in Submicron and Microstructured ZnO Thin Films Obtained by Spin Coating and Chemical Bath Deposition - C. López-Esmerio; C. Ruiz-Rojas; J. Angulo-Rocha; E. Lizárraga-Medina; Francisco Ramos-Brito; E. Camarillo-García; R. Martinez-Martinez; M. Aguilar-Frutis; M. García-Hipólito (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
In the present work the synthesis of ZnO semiconductor thin films was performed successively using spin coating and chemical bath deposition techniques. The deposition was made by varying the concentration of zinc acetate and hexamethylenetetramine (HMTA: ZnAc) in the precursor solution. This process led to two preferred growth directions (002) and (101), both with very similar texture coefficients, too; a noticeable change in morphology of structured surface, variation in unit cell parameters and crystalline grain size. All the films turned out homogeneously submicro and microstructured and with a wurtzite-type hexagonal crystalline structure. Using pre-loaded Mathematica 11.3 software functions and an algorithm developed in it, the micrographies were analyzed to calculate the percentage of substrate-covered area which was always greater than 80%. Likewise, it also found that resistivity decreases at a higher percentage of covered area and that the variation in the shape of the photo luminescent emission spectrum can be considered as a qualitative indication of the concentration of charge carriers.